PENERAPAN METODE WATERFALL PADA SISTEM INFORMASI JASA LAUNDRY (SIJALY) JENSCHAX LAUNDY BEKASI - Mitchell Nere; Duwi Cahya Putri Buani (Jurnal Techno Nusa Mandiri, 2018)
JensChax Laundry is one of the service companies that pioneered its business activities from 2014, since 2014 JensChax Laundry alreadyhas many customers which if JensChax Laundry still uses a conventional system there will be problems in processing data from Customer data to transactions. The solution that can be done for problems that occur in JensChax Laundry is to create a computerized system that is easy to use, with this computerized system is expected to solve any problems that occur. In designing a system not apart from the model used to design the system so that the entire system design is well documented the waterfall model is the best choice for designing a system that is not too large such as the Laundry Service Information System (SIJALY) because the stages are easy to follow and the system designer do not have to hurry enough to follow each stage of the Waterfall model or method.